Um estudo de caso sobre a ciência no Brasil: os trabalhos em fisiologia no Instituto de Ciências Biomédicas e no Instituto de Biociências da Universidade de São Paulo - Navarro, Antonio Coppi (2005)
The purpose of this case study concerning Science in Brazil is pondering about the complexity of the historical process relating to Institutionalization of Science in the country through Papers on Physiology at Biomedical Sciences Institute and at Biosciences Institute of São Paulo University. This way, the study comes to contribute with the History of Science in Brazil, and with the program of Post-Graduation Studies in History of Science at Pontifícia Universidade Católica de São Paulo. On this study, it was intended answering questions of how, historically, occurred the Institutionalization of Physiology at Universidade de São Paulo. Consequently, on the ambit of Science History in Brazil, the analysis has become effective through the conception, on which, the Institutionalization of Science comes to occur through the conjoined manifestation of teaching, research and the publication/ publicizing. And for so, it was accomplished, by means of primary and secondary sources, the internal and external analysis, referring to the process on which the object is inserted. We have concluded that, through Biomedical Sciences Institute and the Biosciences Institute, both, created after the academic reform occurred in Brazil and at Universidade de São Paulo in the 60s, the Institutionalization of Physiology was made possible, as on the period between the 70s and 2000 it became viable in a conjoined manner the Teaching of Physiology at the Bachelor years of Nursing, Physiotherapy, Occupational Therapy, Speech Therapy, Nutrition, Pharmaceutical Sciences, Physical Education, Odontology, Veterinary Medicine, Medicine, Biological Sciences, Psychology courses, and through Researches on the Post-Graduation in Physiology, entitling 296 Masters, 309 PhDs and 37 Academics, besides the publishing of 1087 Articles, 234 Books and the participation in Events with more than 3000 scientific work, whose Teaching, on Research and the Publication run upon studies in level molecular and cellular in the organs in operation on pathological terms or not, in a systemic form and in homeostasis